Assessment of non-response in quality control of nasal septal surgery. Issue 3 (28th February 2019) - Haye, R; Egeland, M T; Døsen, L K; Gay, C; TarAngen, M; Shiryaeva, O
Abstract: Objective: This study evaluated the effect of mail non-response on the validity of the results of nasal septal surgery. Method: Six months post-operatively, questionnaires with both prospective and retrospective ratings were mailed to patients. Patients who did not respond (non-responders) were contacted by telephone. This study compared two cohorts of patients using different interviewers (a nurse and a surgeon). Cohort one consisted of 182 patients (with 67 per cent mail response), and cohort two consisted of 454 patients (with 64.8 per cent mail response). Results: In both cohorts, the improvement in obstruction scores was significantly better among mail responders than among non-responders (telephone interviewees) using prospective ratings, but worse using retrospective ratings. Conclusion: Mail responders had better improvement in nasal obstruction after septoplasty than non-responders. Therefore, low response rates may cause an overestimation of the results. The retrospective ratings obtained through telephone interviews are less reliable because they are influenced by memory and the patients' tendency to give socially acceptable answers.